2024
DOI: 10.3390/healthcare12030359
|View full text |Cite
|
Sign up to set email alerts
|

Listening and Processing Skills in Young School Children with a History of Developmental Phonological Disorder

Nelli Kalnak,
Cecilia Nakeva von Mentzer

Abstract: There is a lack of longitudinal studies on the broad-based outcomes in children with Developmental Phonological Disorder (DPD). The aim of this study was to investigate listening and processing skills in a clinical sample of 7-to-10-year-old children diagnosed with DPD in their preschool years and compare these to same-aged typically developing (TD) children. The Evaluation of Children’s Listening and Processing Skills (ECLiPS) was completed by parents of 115 children with DPD and by parents of 46 TD children.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…Our findings align with previous reports and underscore the utility of CHAPS and APDQ as effective tools for identifying listening difficulties. We concur with the recommendations that questionnaires can be used to identify children at risk for auditory processing disorders (APD) across diverse populations, as supported by the literature [ 10 , 11 , 12 , 15 , 18 , 31 , 32 , 33 ]. Furthermore, our findings add the SSD population to the clinical groups that might benefit from the identification of auditory processing through the CHAPS and APDQ questionnaires [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our findings align with previous reports and underscore the utility of CHAPS and APDQ as effective tools for identifying listening difficulties. We concur with the recommendations that questionnaires can be used to identify children at risk for auditory processing disorders (APD) across diverse populations, as supported by the literature [ 10 , 11 , 12 , 15 , 18 , 31 , 32 , 33 ]. Furthermore, our findings add the SSD population to the clinical groups that might benefit from the identification of auditory processing through the CHAPS and APDQ questionnaires [ 11 , 12 ].…”
Section: Discussionsupporting
confidence: 85%
“…A recent systematic review indicated that APD may be a major underlying factor in children with SSD, as lower scores on auditory processing tasks are often observed in children with varying SSD [ 10 , 29 ]. Kalnak and Nakena von Mentez [ 31 ] reported that children with phonological disorders have significant auditory processing and auditory sensitivity difficulties compared to children with typical development.…”
Section: Discussionmentioning
confidence: 99%